A retrospective review of mucocutaneous infections by human herpesvirus 1 and 2 in an urban population in Malaysia - Hooi, P.S.; Chua, B.H.; Karunakaran, R.; Lam, S.K.; Chua, K.B. (2002)
This is a 10-year retrospective review of mucocutaneous infection by human herpesvirus 1 (HHV1) and human herpesvirus 2 (HHV2) carried out by the virus diagnostic unit of University Malaya Medical Centre (UMMC). A total of 504 specimens from UMMC and a private clinic in the same city (KLSC) were tested; 198 samples from patients with oral lesions and 306 from patients with genital lesions. HHV1 was found to be responsible for 98.4% of oral lesions whereas HHV2 was the cause of 83.6% of all genital lesions. Detailed analysis showed no statistical difference by age group, race or gender among the patients with oral and genital lesions. Two laboratory methods were used in this study. Of the total 504 specimens tested, 18.0% specimen were positive by direct immunofluorescence (IF), 55.0% by virus isolation and 56.5% when both methods were used in combination. Although IF can provide a more rapid diagnosis, it is, however, less sensitive and can be attributed partly to inadequate collection of specimens.